The Influence of the Driving Speed and Vertical Acceleration of the Mobile Machine on the Change of Soil Packing - Artiomov, Mykola; Klets, Dmytro; Boldovskyi, Volodymyr; Makovetsky, Andrii; Kostyk, Kateryna (International Journal of Engineering and Technology, 2018)
The article deals with the processes of changing the vertical forces acting on the propulsion of mobile machines, causing soil compaction when changing the driving speed and vertical accelerations of a mobile machine moving on a deformable soil. The influence of parameters and characteristics of the running gear system of the wheeled tractor, as well as the traction load on the value of vertical accelerations when moving along the soil, is determined. The dependence of the influence of vertical accelerations on the dynamic loads on the axle of the tractor front and rear axles is determined. The dependence of the soil density variation caused by the action of dynamic loads from the propulsion of the tractor front and rear axles has been determined. Â Â